NEW GOLD ORE REGION IN TANZANIA - Mykhailov, V.; Tots, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Tanzania is one of the leading gold mining countries in the world and the discovery of new gold resources on its territory is an actual task. Known gold deposits are concentrated mainly in the northwest of the country, in the metallogenic zone of Lake Victoria, where they are associated with the Archean greenstone belts, and to a lesser extent – in the southwest, in the ore regions of Lupa and Mpanda, confined to the Ubendian Paleoproterozoic mobile belt. With regard to the eastern regions of Tanzania, where the Proterozoic structures of the Uzagaran mobile belt are developed, until recently in this region any significant manifestations of gold mineralization were not known. As a result of our research in the northern part of the Morogoro province of the Republic of Tanzania, a new previously unknown gold deposit Mananila was discovered. It is represented by a large volume, up to 400–450 m long, up to 60–80 m thick, mineralized shear zone over intensely leached and schistosed migmatites, gneisses, amphibolites, penetrated by echelon systems of quartz veins and veinlet, steeply dipping bodies of quartz breccia up to 1.0–1.5 m thick. Gold contents range from 0.61 to 8.11 g/t, the average zone content is 2.5–3.0 g/t. Parallel to the main zone, similar structures are developed on the site, although they are of lower thickness. The forecast resources of the deposit are estimated at 20 tons of gold. 2.8 km to the east from the Mananila field, the recently discovered Mazizi gold deposit is located, and a number of small occurrences of gold are also known in the region. All these objects are located within a large shear zone of the northeastern strike, up to 4–5 km width, over 20 km in length. This serves as the basis for the identification of a new gold ore region in the northern part of the Morogoro province of the United Republic of Tanzania, within the Proterozoic mobile belt of Usagaran, the possible gold content of which has never been previously discussed in geological literature.
Keywords: gold deposit; gold ore region; forecast resources